2010
DOI: 10.1021/jm1003073
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of a Novel Class of γ-Secretase Modulators with PPARγ Activity

Abstract: We present a novel class of dual modulators of gamma-secretase and peroxisome proliferator-activated receptor gamma (PPARgamma) based on the structure of 2-(bis(phenethoxy)pyrimidine-2-ylthio)hexanoic acid 8 (IC(50)(Abeta42) = 22.8 microM, EC(50)(PPARgamma) = 8.3 microM). The modulation of both targets with approved drugs (i.e., amyloid-beta 42 (Abeta42)-lowering NSAIDs for gamma-secretase and glitazones for PPARgamma) has demonstrated beneficial effects in in vitro and in vivo models of Alzheimer's disease (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…The p-trifluoromethyl-phenyl derivative (112) showed inhibitory activity against A 1-42 formation (IC 50 = 6 μM), activation of PPAR (EC 50 = 11μM) and weaker COX1 inhibitory activity (IC 50 = 16.9 μM). The cyclohexyl derivative (113) was the most active in this group, with A 1-42 IC 50 of 5.1 μM and PPAR EC 50 of 6.6μM, but also had higher affinity for COX1 and COX2 (IC 50 COX1 = 13,4 μM, IC 50 COX2 = 10,9 μM) [144]. However, it was also shown that these two active compounds (112,113) do not affect Notch processing or signaling in nontoxic concentrations.…”
Section: Dual Acting Hybrids --Secretase Modulators With Ppar Activitymentioning
confidence: 86%
See 1 more Smart Citation
“…The p-trifluoromethyl-phenyl derivative (112) showed inhibitory activity against A 1-42 formation (IC 50 = 6 μM), activation of PPAR (EC 50 = 11μM) and weaker COX1 inhibitory activity (IC 50 = 16.9 μM). The cyclohexyl derivative (113) was the most active in this group, with A 1-42 IC 50 of 5.1 μM and PPAR EC 50 of 6.6μM, but also had higher affinity for COX1 and COX2 (IC 50 COX1 = 13,4 μM, IC 50 COX2 = 10,9 μM) [144]. However, it was also shown that these two active compounds (112,113) do not affect Notch processing or signaling in nontoxic concentrations.…”
Section: Dual Acting Hybrids --Secretase Modulators With Ppar Activitymentioning
confidence: 86%
“…A novel class of dual modulators of -secretase and peroxisome proliferator-activated receptor (PPAR ) were presented by Hieke et al [144]. One of the main objectives of this study was to develop a potent dual modulator with weaker cyclooxygenase (COX) inhibitory activity compared to non-steroidal anti-inflammatory drug (NSAIDs)-type -secretase modulators (GSM).…”
Section: Dual Acting Hybrids --Secretase Modulators With Ppar Activitymentioning
confidence: 99%
“…Monoclonal antibody IC16 raised against residues 1–15 of the human Aβ sequence, HRP-coupled carboxyl terminus-specific Aβ antibodies BAP24, BAP15 and BAP29 specific for Aβ40, Aβ42, and Aβ38, and polyclonal antibody CT15 against the last 15 C-terminal amino acids of human APP have been described previously [22], [40]. Monoclonal antibody PSN2 against a synthetic peptide corresponding to amino acids 31–56 of human PSEN1 was kindly provided by Dr. Hiroshi Mori [41].…”
Section: Methodsmentioning
confidence: 99%
“…The investigated pirinixic acid derivatives modulate 5-LO, mPGES1, PPARα, and PPARγ at varying potencies [3][4][5][6][7][8] and these molecules are considered as potential anti-cancer drug targets [14][15][16][17]. However, the effects of the compounds on cancer cell viability did not correlate Table 8. with their effects on 5-LO, mPGES1, PPARα, or PPARγ activity (Suppl .…”
Section: Discussionmentioning
confidence: 99%